Realization of a 1-bit RF receiver - An implementation method for distributed MIMO over fiber - Aabel, Lise (My University, 2019)
Development of wireless networks enforce research on new system designs, always in pro fit of improving certain features. A distributed MIMO network is de fined by moving the antennas away from the base station, gaining spatial degrees of freedom. This technique has proven to meliorate some of the experienced diffculties in a collocated MIMO system, inspiring further research. In profi t of understanding the capacity and limitations of such a network it is advantageous to enable actual measurements by building a testbed. Further, 1-bit receiver technology is promising in reducing analog system complexity, migrating as much as possible to digital domain at the central unit. This project entails research on the implementation of a distributed MIMO 1-bit RF receiver, including measurements and hardware analysis. It proves that such a system is in fact realizable with off-the-shelf components, although demands further development to gain exibility.